Potret Pemahaman Bendahara Pemerintah Dalam Implementasi Pemotongan PPh Pasal 21 - Lestari, Yeni Puji; Chamalinda, Khysh Nusri Leapatra (Jurnal Paradigma Ekonomika, 2024)
This study aims to evaluate the understanding of government treasurers in the implementation of the calculation and reporting of Income Tax Article 21 at the Bangkalan Regency Education Office. The research method used is descriptive qualitative with a case study approach. This research was conducted at the Regional Office of Education of Districts X and Y in Bangkalan Regency. The data source of this research consists of primary and secondary data. For data collection, in-depth interviews were conducted with respondents relevant to the research topic. The results of the findings of this study indicate that the treasurer of the Regional Office of Education in Districts X and Y has understood and implemented the calculation and deduction of Income Tax Article 21 by system. However, the treasurers still need to improve their understanding of the progressive rate of Income Tax Article 21.